The Profile of Students’ Mathematical Communication Ability on Statistics Based on Adversity Quotient - Amelia Okta Viyani; Rizky Esti Utami; Agnita Siska Pramasdyahsari (International Journal of Research in Education, 2022)
Mathematical communication skills have an important role in human life because humans are social creatures who cannot live individually but always relate and need other people. This type of research is descriptive qualitative research. This study aims to determine the profile of students' mathematical communication skills on statistical material in terms of Adversity Quotient (AQ) which are climbers (high), campers (medium), and quitters (low). This research was conducted on students of class XII MIPA 1 SMA Laboratorium UPGRIS. The research subjects were 6 students consisting of 2 subjects with climbers type (high), 2 subjects with campers type (medium), and 2 subjects with quitters type (low). The instrument used in this research is the ARP Adversity Quotient questionnaire and uses a communication skill test. The data analysis technique was carried out in 3 stages, namely data reduction, data display, and conclusion drawing/verification. The validity of the data using source triangulation. The results of this study indicate that (1) Subjects with the quitters type have not met all indicators of communication skills including written text, drawing, and mathematical expression; (2) Subjects with the campers type meet the indicators of mathematical communication skills, namely written text and drawing, but do not meet the indicators of mathematical expression; (3) Subjects with the climbers type fulfills all indicators of mathematical communication skills including written text, drawing, and mathematical expression.